Factors Influencing Public Perceptions of the Covid-19 Booster Vaccine Program in Biringkanaya District, Makassar City - Daming, Nursuci Muhsanah; Samsualam, Samsualam; Abbas, Jasmin (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2022)
Background: Efforts to break the chain of the spread of Covid-19 require good understanding and knowledge from all elements, including the community. Perception is a result of curiosity through sensory processes, especially in the eyes and ears of certain objects. Perception is also the most important domain in the formation of behavior. A person's perception is influenced by several factors, including the level of knowledge, education, occupation, age, environmental factors, and sociocultural factors. This study aims to analyze the factors that influence public perception of the Covid-19 booster vaccine program in Biringkanaya District, Makassar City. Methods: This research is a quantitative study using a cross-sectional design. In this study, there were 100 respondents who were obtained from direct interviews and filling out questionnaires. Data analysis used univariate test analysis, bivariate test (Chi-Square), and multivariate test. Results: The results of this study indicated that out of 100 respondents, 78 respondents (78%) had a positive perception of the Covid-19 booster vaccine program and 22 respondents (22%) had a negative perception of the Covid-19 booster vaccine program. The variable that influences public perception of the Covid-19 booster vaccine program is the willingness to be vaccinated (P=0.000). Then the variable willingness to be vaccinated has a dominant influence on public perception of the Covid-19 booster vaccine program with a p-value of 0.000; OR = 15,000; 95% CI = (4.497 – 50.035). Respondents who are willing to be given the vaccine are 15 times easier to receive the Covid-19 booster vaccine than people who are not willing to be vaccinated.